Phytochemical Composition and Antioxidant Activities of Phosphate Buffered Saline and Aqueous Extracts of Aloe barbadensis Miller Leaf Latex and Gel from Three Counties of Kenya - Nakiguli, Caroline K.; Kosgei, Viola J.; Cherutoi, Jackson K.; Odda, John (Asian Journal of Applied Chemistry Research, 2022)
Aims: Aloe barbadensis Miller (A. barbadensis) is one of the most treasured species from the Aloe genus that has been used in management of various ailments. However, there are few reports on the secondary metabolites, total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activities of its leaf latex and gel. This study aimed at comparing the phytochemicals and antioxidant activity of phosphate buffered saline (PBS) and distilled water extracts of latex and gel of A. barbadensis leaves from Kisumu, Elgeyo Marakwet and Baringo Counties of Kenya, East Africa. Study Design: The study employed quantitative and qualitative research designs Place and Duration of Study: This study was conducted at the Department of Chemistry and Biochemistry, School of Sciences and Aerospace Studies, Moi University, Eldoret, Kenya between May 2021 and August 2021. Methodology: Leaf samples were extracted by maceration using distilled water and PBS. Phytochemical screening was performed following standard screening procures while TPC, TFC and antioxidant activity were determined using Folin-Ciocalteau method, Aluminum Chloride colorimetric assay and DPPH radical scavenging assay, respectively. One-way analysis of variance (ANOVA) was performed with Tukey post hoc test at P = .05. Correlations among TPC, TFC and antioxidant activity of the extracts were assessed using Pearson’s bivariate correlation. The analyses were performed using GraphPad Prism for windows (v9.0, GraphPad Software, California, USA). Results: Phytochemical screening results indicated the presence of alkaloids, phenols, saponins, flavonoids, cardiac glycosides, tannins, steroids, terpenes and quinones as the main secondary metabolites in the extracts. TPC and TFC were found to be highest for the aqueous extracts, with the highest contents (102.393 ± 0.121 mg GAE/ g DW and 47.228 ± 0.248 mg QE / g DW) being for dry latex of leaves from Baringo. The highest antioxidant activity (IC50 = 21.900 ± 0.0594 mg/mL) was for aqueous extract of fresh latex of leaves from Baringo, followed by those from Elgeyo Marakwet and then Kisumu. Conclusion: This study established that dry and fresh latex and gel extracts of A. barbadensis leaves possess therapeutic phytochemicals with antioxidant activities, which support their use in traditional phytomedicine in Kenya.
Keywords: Total polyphenols; Aloe vera; DPPH assay; secondary metabolites